Trends in Asian water environmental science and technology - Kurisu, Futoshi; Ramanathan, A. L.; Kazmi, Absar Ahmad; Manish Kumar (Springer, 2016)
This book brings together and integrates contributions on water quality modeling, monitoring and assessment techniques; wastewater treatment technologies; and sociological approaches in a single text. Divided into twenty chapters, it offers a comprehensive reference for students, professionals and researchers working on various aspects of water environment technology. The papers published in this book - selected from those presented at the 1st International Forum on Asian Water Environment Technology, held in 2013 in New Delhi, India - highlight the water environmental problems in Asia and respective countermeasures. This book addresses water quality requirements, emphasizing the factors that affect the water environment. Treated wastewater as a new source of water is also examined, introducing readers to important aspects of water reuse. Selecting the most effective and proper wastewater treatment approach is actually the most essential part of generating a new water resource, as well as protecting the receiving water environments. Thus, the fundamental principles of wastewater treatment and monitoring are a major focus in this book, which is intended to help readers effectively address various water environmental problems in Asian countries.- Resumé vydavatel
Includes index.
Keywords: kvalita vody -- Asie; znečištění vod -- Asie; čištění odpadních vod -- Asie; water quality -- Asia; water pollution -- Asia; sewage purification -- Asia; elektronické knihy; sborníky; electronic books; papers of several authors